Migratory DCs activate TGF-β to precondition naive CD8(+) T cells for tissue-resident memory fate - Mani, Vinidhra (Science, 2019)
Epithelial resident memory T (eT(RM)) cells serve as sentinels in barrier tissues to guard against previously encountered pathogens. How eT(RM) cells are generated has significant implications for efforts to elicit their formation through vaccination or prevent it in autoimmune disease. Here we show that during immune homeostasis, the cytokine TGF-β epigenetically conditions resting naive CD8(+) T cells and prepares them for the formation of eT(RM) cells in a mouse model of skin vaccination. Naive T cell conditioning occurs in lymph nodes (LNs), but not in the spleen, through MHC I-dependent interactions with peripheral tissue-derived migratory dendritic cells (DCs) and depends on DC-expression of TGF-β-activating αV-integrins. Thus, the pre-immune T cell repertoire is actively conditioned for a specialized memory differentiation fate through signals restricted to LNs.